Interventions to promote mobility and quality of life in nursing homes: A systematic review - Benjamin Bohn; Steve Strupeit (Wiley, 2023)
Abstract Aim The aim of the study was to identify interventions to promote mobility that has an impact on the quality of life of people living in nursing homes and assisted living facilities. Design The design of the study was a systematic review. Methods The search was performed in September 2021 in the databases PubMed, Epistemonikos and the Cochrane Library for studies published between 2010 and 2021 in the German or English language. Results Four studies identified improvements in mobility and quality of life. Nine of the ten included studies showed impacts of the interventions on different mobility variables. Heterogeneous variables and instruments were used to assess quality of life and, in particular, mobility, which made it difficult to compare the results of the studies. Approximately 50% of the identified studies had small sample sizes.